Service Encounter Front Office Di Yogyakarta Marriott Hotel - Nadya Awaludini (Jurnal Indonesia Sosial Teknologi, 2024)
Service encounter implemented at Yogyakarta Marriott Hotel, one of the leading five-star hotels in Yogyakarta, Indonesia. Aspects such as interaction with the receptionist, room service, food and beverage service, and complaint handling were analyzed to identify their contribution to building a satisfying guest experience. The hotel utilizes modern technology and implements high service standards to improve efficiency and personalization of service. The findings indicate that the implementation of effective service encounters at Yogyakarta Marriott Hotel plays a significant role in enhancing guest satisfaction and customer loyalty. Well-trained staff, spontaneous actions, and responsive problem-solving skills contribute to creating a memorable stay experience. Efficient check-in and check-out processes, 24/7 room service, and informative concierge services are integral parts of the service encounter offered by this hotel. In addition, personalization of service and small gestures such as surprises for special moments build positive relationships with guests. The study concluded that the implementation of superior service encounters provides significant added value, strengthening the image of Yogyakarta Marriott Hotel as a premier hospitality destination in Yogyakarta. The hotel successfully meets guest expectations by providing a high-quality service experience, which differentiates it from competitors in the hospitality industry.